Kunjungan dan Promosi UMKM Sebagai Strategi Peningkatan Ekonomi Di Desa Sait Buttu Saribu - Andrian Febriansyah; Fittrah Mirza; Siti Aisyah (Pusat Riset dan Inovasi Nasional, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting the Indonesian economy, especially in rural areas where they contribute significantly to employment and local income. Sait Buttu Saribu Village in Simalungun Regency possesses considerable potential in the agricultural, tourism, and culinary sectors, which can be developed through strong MSME activities. Nevertheless, many local MSMEs continue to experience challenges related to limited promotion, weak branding, and restricted market access. This study aims to analyze visit-based and promotional strategies for MSMEs as an effort to strengthen the village economy and enhance business competitiveness. The research methods consist of a literature review of relevant previous studies and field observations conducted through community service activities in the village. The findings indicate that industrial visits, digital promotion via social media platforms, the utilization of Google Maps for location visibility, and branding that highlights local wisdom are effective strategies for expanding market reach and increasing MSME competitiveness. Through strong synergy among the village government, MSME actors, and the local community, MSMEs in Sait Buttu Saribu Village can grow more optimally and contribute to sustainable economic development and tourism.